Prospective, rétrospective et perspective : un essai de modélisation du temps - Valaskakis, Kimon (L'Actualité économique, 1975)
The purpose of this paper is to show that an essential symmetry exists between the "history of the future" (prospective) and the history of the past (retrospective) and that only by reference to both can we fully understand the present. The exploratory look into both the future and the past implies a model of time. This model is presented in a diagram entitled the "chronosphere" and involves a vision of time punctuated by the freedom to make decisions. In the very-short-run all factors are fixed. In the very long-run all factors are variable. In between there are five discernible time periods. The study of time itself implies model-building and scenario-writing. Both are analysed and elements of a methodology for future studies are put in place. The article ends with an exhortation to further "marry" the scenario-technique (essentially a creative process) with the modelling-technique (which is primarily a scientific procedure).